Electrocardiography Characteristics of Isolated Non-Compaction of Ventricular Myocardium in Japanese Adult Patients - Yamashita, Takeshi; Uejima, Tokuhisa; Sawada, Hitoshi; Otsuka, Takayuki; Semba, Hiroaki; Isobe, Mitsuaki; Asada, Kazuo; Sagara, Koichi; Aizawa, Tadanori; Shoji, Masaaki (Circulation Journal, 2010)
Background: Isolated non-compaction of ventricular myocardium (INVM) is characterized by persistent embryonic myocardial morphology without other cardiac anomalies. Congestive heart failure, critical arrhythmias, and systemic thromboemboli are known as major manifestations during childhood. Recently it was reported that there are some patients who seem apparently healthy in adult INVM. Clinical characteristics including that for electrocardiograms (ECG) of adult INVM, however, are unknown for Japanese subjects. Methods and Results: From 24,082 patients who underwent echocardiography between June 2000 and June 2007, 187 patients (0.78%, 41.3±16.8 years, 122 male) were identified as having INVM according to the criteria proposed by Oechslin et al. Although fatal ventricular arrythmias and thromboembolic events occurred in 2 patients and in 1 patient, respectively, the rest had no severe cardiac complications. Normal ECG findings were found only in 24.6% of the patients. Most of the ECG abnormalities, however, were non-specific: ST-T changes in 35.2% and bundle branch block in 14.9%. Notably, Brugada-like ECG was frequently seen in the present Japanese INVM patients (3.2%). The incidence of these ECG findings was not dependent upon the extent of non-compaction. Conclusions: The prevalence and ECG findings of adult Japanese INVM patients in a hospital-based clinical practice have been identified.  (Circ J 2010; 74: 1431 - 1435)